Multienergy CT acquisition and reconstruction with a stepped tube potential scan. Issue 1 (23rd December 2014) - Shen, Le; Xing, Yuxiang
Abstract : Purpose: Based on an energy‐dependent property of matter, one may obtain a pseudomonochromatic attenuation map, a material composition image, an electron‐density distribution, and an atomic number image using a dual‐ or multienergy computed tomography (CT) scan. Dual‐ and multienergy CT scans broaden the potential of x‐ray CT imaging. The development of such systems is very useful in both medical and industrial investigations. In this paper, the authors propose a new dual‐ and multienergy CT system design (segmental multienergy CT, SegMECT) using an innovative scanning scheme that is conveniently implemented on a conventional single‐energy CT system. The two‐step‐energy dual‐energy CT can be regarded as a special case of SegMECT. A special reconstruction method is proposed to support SegMECT. Methods: In their SegMECT, a circular trajectory in a CT scan is angularly divided into several arcs. The x‐ray source is set to a different tube voltage for each arc of the trajectory. Thus, the authors only need to make a few step changes to the x‐ray energy during the scan to complete a multienergy data acquisition. With such a data set, the image reconstruction might suffer from severe limited‐angle artifacts if using conventional reconstruction methods. To solve the problem, they present a new prior‐image‐based reconstruction technique using a total variance norm of a quotient image constraint. On the one hand, the prior extracts structural information from all of the projection data. On the other hand, the effect from a possibly imprecise intensity level of the prior can be mitigated by minimizing the total variance of a quotient image. Results: The authors present a new scheme for a SegMECT configuration and establish a reconstruction method for such a system. Both numerical simulation and a practical phantom experiment are conducted to validate the proposed reconstruction method and the effectiveness of the system design. The results demonstrate that the proposed SegMECT can provide both attenuation images and material decomposition images of reasonable image quality. Compared to existing methods, the new system configuration demonstrates advantages in simplicity of implementation, system cost, and dose control. Conclusions: This proposed SegMECT imaging approach has great potential for practical applications. It can be readily realized on a conventional CT system.